Influence of Boer goats for crossing with Tanzanian goats - Mchau, K.W. (1979)
The high demand for animal protein in Tanzania highlights the need for livestock improvement. Because of its large numbers, increased productivity of the Tanzania goat would result in a substantial increase in the total supply of meat. Crossing indigenous goats with improved meat breeds is considered one of the quick methods for achieving this goal. Records on 210 kids born in the period from 1958 to 1961 were analysed to study the influence of the Boer goat as a potential improver breed. The kids belonged to five genetic groups namely half-bred, ¾ Boer, 7/8 Boer and purebred Boer kids - all sired by imported Boer bucks and Tanzania kids. All groups were raised under the same environment and recorded up to two years of age. Crossbred kids had significantly higher birth weights, growth rates and weights-for-age than Tanzania kids. ¾ Boer kids tended to have the highest performance with an average superiority over Tanzania kids ranging between 30 and 50 percent for the three traits. Twinning and mortality rates increased with the level of Boer blood. The twinning frequency among Tanzania, half bred, ¾ Boer and purebred Boer goats was 17, 37, 33 and 58 percent, respectively. Corresponding figures for mortality up to two years of age were 11, 21, 32 and 50 percent for the four groups, respectively. Trypanosomiasis, Helminthiasis, and pneumonia were the most frequent specific causes of death. The main influence of the Boer on slaughter characteristics was to increase the proportion of the Boer on slaughter characteristics was to increase the proportion of carcass bone. Direct Boer effects explained about 70 to 80 percent of the average superiority of crossbred and purebred Boer goats in twinning rate, weaning weight, yearling weight and mortality rate. Maternal effects seem to have been important for birth weight while heterosis was probably important for weight at 2 years of age in the halfbreds. Heterosis for maternal effects was of little account in all traits except, possibly for weaning weight. Under the condition of the experiment the most profitable operation seems to be the production of ¾ Boer kids by back crossing halfbred females. However, such a system would require a continuous importation of Boer bucks or maintenance of purebred Boer populations in Tanzania. While the first option is economically unsound, the latter is precluded by the apparently low survival rates of purebred Boer under Tanzanian conditions. Hence the formation of gene pools at ¾ Boer level for upgrading the local population was suggested as a possible means of utilizing Boer genes at the national level.